4E analysis and multiple objective optimizations of a cascade waste heat recovery system for waste-to-energy plant. (15th February 2021) - Pan, Mingzhang; Lu, Fulu; Zhu, Yan; Li, Hao; Yin, Jiwen; Liao, You; Tong, Chengzheng; Zhang, Fengyi
Highlights: A novel waste heat recovery system is proposed based on WTE plant. A comprehensive thermodynamic analysis of the system is conducted. Based on NPV, the dynamic payback period of new WTE plant is studied. Sensitivity analysis as well as multi-objective optimization are employed. The system levelized cost of electricity and ecological efficiency are studied. Abstract: Owning to its advantage in waste reuse, waste-to-energy technology, has become the most popular way to deal with the increasingly municipal solid waste. However, the energy efficiency of waste-to-energy plant is limited because of the huge heat loss. In this study, a novel waste heat recovery system, consisting of a supercritical CO2 cycle, an organic Rankine cycle, and an absorption refrigeration cycle, is proposed to improve both the thermal efficiency and economic performance of the waste-to-energy plant. A comprehensive thermodynamic analysis is performed to study the energy and exergy efficiency of the system by establishing a reliable mathematical model. Net present value analysis is carried out to study the final net profit and dynamic investment payback period. Besides, the levelized cost of electricity and ecological efficiency of the waste-to-energy plant are investigated. Based on the results of parameter sensitivity analysis of the system, multiple objective optimizations is carried out by using non-dominated sorting genetic algorithm-II. The results show that the combined system obtains the highest economic benefit in winter. The energy efficiency of the waste-to-energy plant can be up to 75.07% after adding the waste heat recovery system, with an increment of 54.58%. And the maximum net present value and minimum dynamic payback period are 23.22 M$ and 4.11 years, separately. Compared with the original waste-to-energy plant, the levelized cost of electricity and ecological efficiency are decreased by 68% and increased by 16%, respectively. From the results of sensitivity analysis, the isentropic efficiency of turbine of supercritical CO2 cycle, the evaporator pressure of organic Rankine cycle, and the generator temperature of absorption refrigeration cycle are the most sensitive factors for the thermal efficiency and economic performance of the system. The exergy destruction analysis shows that the exergy destruction rate of the boiler declines to 48.41% after adding the waste heat recovery system, but the condensers need further improvement for their lowest exergy efficiency. In conclusion, the waste-to-energy plant can provide electricity, heating and cooling simultaneously after adding the waste heat recovery system and the proposed system is theoretically feasible from the results of thermodynamic, economic and environmental analysis.